Célestin Freinet: história, política, princípios, técnicas e pesquisas acadêmicas (1982-2018) - Martins, Gabriela Luchesi (Universidade Federal de São Carlos, 2022)
The present work has as its theme Freinet Pedagogy and academic research (theses and dissertations), between 1982 and 2018, which address theory and practice in the classroom. Célestin Freinet believed that techniques and practices would change according to the social, historical, political and cultural issues of a given time. Based on this premise and our personal experience with this Pedagogy, we chose our research theme and arrived at the following question: what transformations in the teaching and learning process can be perceived in Brazilian academic research between 1982 and 2018, based on the Freinet Pedagogy, who use techniques and practices in the classroom, in Elementary School I? From this, we set the following objectives: to know the academic research on Freinet produced in Brazil; discriminate which researches involve freinetian techniques and practices in Elementary School I; and to analyze the transformations that occurred in academic research in the teaching and learning process of Freinet techniques and practices in Elementary School I. For data collection, we used a bibliographical review as a methodology, based on the analysis of academic works, with a search in the Database Data from the CAPES Portal. We categorize and organize the research in tables and graphs, finally we have 9 works that were found in those that involve the teaching and learning process in the classroom, in elementary school I and that bring as a theme the pedagogical practices, techniques and freinetian principles . We find in the post-2000 works the connection with Marxist-based theories – Freire, Vygostsky, Pacheco, Wallon – different from those prior to that period that had their focus on Freinet. It appears that the essence of Freinet Pedagogy, its principles, remain until today, like a seed that germinates and bears fruit, spreading, sprouting in fertile soil.
Célestin Freinet: history, politics, principles, techniques and academic research (1982-2018)
Keywords: Célestin Freinet; Práticas pedagógicas; Política e educação; Ensino fundamental I; Celestin Freinet; Pedagogical practices; Politics and education; Elementary school I; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO